Pengaruh Media Arcademics terhadap Minat Belajar Matematika Peserta Didik di SD Miftahussadah - Badawi, Munawir; Erna Zumrotun (Eksponen, 2024)
The use of learning media that is easy to make and use is needed by teachers along with technological advances. Learning media has a significant influence on the learning process. Observations at Miftahussadah Elementary School in Gebog Subdistrict show that although learning is quite varied, conventional methods without the help of media are still often used. Students' learning motivation is a determining factor in learning activities. The more interesting the learning media used, the higher the tendency and attention of students in learning. This study aims to see the effect of Arcademics media on students' interest in learning. This study used a one group pretest-posttest pre-experiment design. The sampling technique was purposive sampling with a total of 14 students from class V SD Miftahussadah. Data analysis includes validity and reliability tests, normality tests, homogeneity tests (Levene's test), and t-tests with the help of SPSS applications. The results showed that the use of Arcademics media had a positive influence on students' learning motivation.